Association of 17β-HSD3 with steroidogenesis-related gene expression and primordial germ cell development in ducks - Li Li; Xiaopan Liu; Linli Zhang; Liang Huang; Zhongwei Miao; Zhiming Zhu; Qinlou Huang; Qingwu Xin; Nenzhu Zheng (Theriogenology, 2026)

Multi-omics reveals metabolic division of labor in mixed-starter soymilk fermentation - Jiahui Li; Jiahui Yang; Linli Zhang; Tonghao Du; Zhen Peng; Shijin Xiong; Muyan Xiao; Tao Xiong; Mingyong Xie (Food Research International, 2026)

Peri-implantation 6PPD-Q exposure impairs endometrial decidualization and induces pregnancy loss - Wanting Fu; Ziyao Yang; Yi Li; Tianxiao Chen; Qingling Yang; Linli Hu (Journal of Hazardous Materials, 2026)

Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

Portulaca Oleracea polysaccharides attenuate zearalenone-induced macrophage activation and Leydig cell dysfunction in testis: A single-cell and multi-omics study - Bingxin Huangfu; Yanan Chen; Jie Li; Ranyue Xu; Yijia Zhao; Linli Cheng; Xiaoyun He; Kunlun Huang (Food Research International, 2026)

Overcoming mechanical and moisture barriers: A novel rice protein/sodium alginate packaging film based on gelatin and PDMS - Linli Wei; Xiaoli Qin; Jingwen Li; Xinjia Zhou; Xiong Liu; Jinfeng Zhong (Food Chemistry, 2026)

The first toxicological assessment of copper exposure in Cipangopaludina cathayensis: Integrative insights from gut microbiota and hepatopancreas responses - Linli Li; Jinyou Wei; Yufan Deng; Jing Yu; Xiayun Wei; Weiying Wang; Jiamin Chen; Jing Wei; Tiantian Yuan; Haizhen Tan; Zhengjun Wu; Jiaoyun Jiang (Environmental Pollution, 2026)

Chinese AgroMeteorological Model CAMM 2.0–3.0: System Framework, Mechanistic Innovations, and Operational Applications - Yuping Ma; Dingrong Wu; Jianying Yang; Youhao E; Qi Wang; Shuang Sun; Linli Sun; Min Xu; Dianchen Han; Yang Li; Yuanda Zhang; Qianchuan Mi; et al. (Journal of Meteorological Research, 2026)

Optimal production strategies for balancing yield enhancement, carbon sequestration, and soil greenhouse gas flux regulation in Chinese maize systems under straw return and organic fertilizer application - Linli Zhou; Dongping Shen; Keru Wang; Ruizhi Xie; Yuqin Zhang; Bo Ming; Jun Xue; Guoqiang Zhang; Shaokun Li (European Journal of Agronomy, 2026)

BAMBI modulates proliferation, apoptosis, and hormone secretion in Jinding duck granulosa cells - Li Li; Xiaopan Liu; Changtao Liu; Chengfu Pan; Linli Zhang; Qingwu Xin; Zhongwei Miao; Liang Huang; Yuwei Li; Yaping Zhang; Qinlou Huang; Nenzhu Zheng; et al. (Animal Reproduction Science, 2026)

Creating precise Cd(II)-targeted site through bioinspired tannic acid-modified coal gangue-derived zeolite for enhancing Cd(II) immobilization from aqueous solutions - Yuzhi Zhou; Linli Long; Jingyu Sun; Zongyao Li; Jingwei Niu; Jinming Duan; Min Chen; Boyu Wang; Xiaoyang Chen (Process Safety and Environmental Protection, 2026)

Relationship between DNA methylation and ethylene in plants: A review - Xinmeng Geng; Zesheng Liu; Caiting An; Min Cao; Qi Wang; Mengkun Liu; Qianbing Li; Chunlei Wang; Linli Hu (Plant Science, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Achieving synergistic improvements in maize yield and nitrogen use sustainability through a novel high-density production system enabled by precision stage-specific regulation - Liang Fang; Dongping Shen; Zhen Wang; Linli Zhou; Tingting Zhang; Guoqiang Zhang; Jun Xue; Ruizhi Xie; Peng Hou; Keru Wang; Bo Ming; Ling Gou; et al. (European Journal of Agronomy, 2026)

Multi-omics characterization of benzo[a]pyrene toxicity networks identifies SERPINE1 and STK3 as prognostic biomarkers and therapeutic targets in head and neck squamous cell carcinoma - Yan Guo; Jiarui Zhang; Jingchun Ge; Liang Li; Ming Liu; Linli Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Acid-induced structural reorganization of fish myofibrillar protein gels: trade-off between elasticity and stability - Linli Fang; Ruoyi Hao; Xinlin Liu; Xianbing Xu; Shengjie Li; Xuanpeng Wang; Dan Wang; Yugang Wang; Hairong Sun; Xiuping Dong; Jinfeng Pan (Food Research International, 2026)

Temperature as a determinant of symbiodiniaceae health: physiological, antioxidant, and metabolic responses under co-exposure to microplastics - Tan Haizhen; Tian Wenfei; Liu Tingting; Li Lixiang; Ye Quanqing; Wei Jinyou; Li Linli; Wei Fen; Jiang Jiaoyun (Marine Environmental Research, 2026)

Multifunctional RP/SA bilayer film with oregano essential oil and anthocyanins: Properties enhancement mechanism and application in pork - Huimei Zhu; Jingwen Li; Xiaoli Qin; Linli Wei; Jinfeng Zhong (Food Chemistry, 2026)

Foodborne diarrhea outbreaks linked to Citrobacter species in East China 2022–2023 - Guilai Jiang; Changyuan Guo; Xin Kuai; Linli Ji; Jun Zhao; Yuxuan Zhou; Xiaolong Wang; Menghan Zhang; Zhemin Zhou; Heng Li (Food Microbiology, 2025)

Polystyrene nanoplastics induce ovarian injury by PI3K-Akt pathway-driven macrophage extracellular trap formation - Yingying Chen; Linli Yang; Yuanyuan Li; Lulu Si; Hanlin Fu; Tianjiao Lai; Ruixia Guo (Environmental Pollution, 2025)

Mining of trace natural products from Pyrrosia calvata with feature-based molecular network strategy - Yan Li; Boquan Qu; Dian Liu; Feifei Huang; Linli Xu; Yanfang Liu (Biochemical Systematics and Ecology, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Elucidating microbial succession dynamics and flavor metabolite formation in korean style spicy cabbage fermentation: Integration of flavoromics, amplicon sequencing, and metagenomics - Mingwei Zhao; Shijin Xiong; Tonghao Du; Xiaoyan Xu; Huiyu Li; Linli Zhang; Yazhou Xu; Tao Wei; Tao Xiong; Mingyong Xie (Food Chemistry, 2025)

Time-series NDVI and greenness spectral indices in mid-to-late growth stages enhance maize yield estimation - Dayun Feng; Hongye Yang; Kexin Gao; Xiuliang Jin; Zhenhai Li; Chenwei Nie; Guoqiang Zhang; Liang Fang; Linli Zhou; Huirong Guo; Zhijie Jia; Bo Ming; et al. (Field Crops Research, 2025)

Ceritinib (LDK378) inhibits laryngeal squamous cell carcinoma progression via regulating ROS-induced mitochondrial apoptosis and inducing oxidative stress - Yue Wang; Xiaoli Ren; Pengyan Liu; Ran An; Wenjing Li; Licheng Xu; Yaoyao Dong; Xiaolin Xu; Yi wang; Lei Zhang; Linli Tian (Toxicology and Applied Pharmacology, 2025)

Correction: Testing the validity of the Montgomery–Koyama–Smith equation and the power law equation using 3231 tepals of a Magnolia species - Linli Deng; Jinfeng Wang; Li Zhang; Dirk Hölscher; Peijian Shi (Trees, 2025)

Response of rice flower carp (Cyprinus carpio var.) to high-temperature stress: Mechanisms and limits of tolerance - Chunxing Cheng; Wenfei Tian; Jinyou Wei; Linli Li; Haizhen Tan; Zhengjun Wu; Jiaoyun Jiang (Journal of Thermal Biology, 2025)

Testing the validity of the Montgomery–Koyama–Smith equation and the power law equation using 3231 tepals of a Magnolia species - Linli Deng; Jinfeng Wang; Li Zhang; Dirk Hölscher; Peijian Shi (Trees, 2025)
Key message The power-law equation provides marginally better accuracy than the Montgomery–Koyama–Smith equation for estimating total tepal area, with flexible definitions of maximum tepal length maintaining prediction reliability. Abstract Montgomery–Koyama–Smith equation (MKSE) and power law equation (PLE) were evaluated for estimating the total tepal area ( A T ) of Magnolia × soulangeana flowers using 3231 tepals from 359 flowers. MKSE assumes an isometric relationship between the A T and the product of summed tepal widths ( L KS ) and maximum tepal length ( W KS ), while PLE incorporates an allometric scaling exponent (α). Results showed α = 0.9561 (95% CI 0.9481–0.9641), confirming allometry. PLE exhibited slightly lower root-mean-square error (RMSE: 0.0149 vs. 0.0172) and mean absolute percentage error (MAPE: 1.18% vs. 1.35%) than MKSE. Redefining W KS as a random selection from the largest 9, 6, or 3 tepal lengths per flower minimally affected model performance, with MAPE consistently below 5% even when sampling the entire length range. This flexibility simplifies field measurements without compromising accuracy. Variability in geometric series common ratios across flowers likely drives the observed allometric scaling. This study validates that A T can be reliably estimated using summed widths and a flexibly defined maximum length, emphasizing PLE’s marginally superior fit. These findings advance methods for non-destructive floral trait quantification in species with fixed organ counts.

Flexural behavior of steel plate-UHPC composite wet joints for precast UHPC deck slabs - Minghong Qiu; Zongxuan Shao; Banfu Yan; Youshan Liu; Linli Duan; Zhao Li (Engineering Structures, 2025)

Carbon dots modified metallated graphdiyne with enhanced electron transfer and O2 adsorption capacity for efficient H2O2 photoproduction - Honglin Si; Mude Zhu; Zenan Li; Jiaxuan Wang; Jiacheng Li; Linli Xu; Hui Huang; Yang Liu; Wai-Yeung Wong; Zhenhui Kang (Chemical Engineering Journal, 2025)

OsBSK3 and OsBSK2 regulate grain size and leaf angle via MAPK signaling pathway in rice - Xin Jin; Linli Fu; Chunxiao Chen; Jiali Liu; Yingxiang Liu; Wei Zhang; Xiufeng Li; Changhua Liu; Qingyun Bu; Xiaojie Tian (Theoretical and Applied Genetics, 2025)

Transport and action of sesame protein-derived ACE inhibitory peptides ITAPHW and IRPNGL - Tonghao Du; Jiahui Yang; Yuan Qin; Xizhuo Huang; Jiahui Li; Shijin Xiong; Xiaoyan Xu; Linli Zhang; Mingwei Zhao; Huiyu Li; Tao Huang; Tao Xiong; et al. (Food Chemistry, 2025)

Based on the resting-state functional magnetic resonance imaging reveals the causal relationship between the brain function network and the risk of tinnitus: a bidirectional Mendelian randomization analysis - Yuchao Liu; Chunli Li; Linli Yao; Yuan Tan; Lu Shi; Pei Chen (Brain Imaging and Behavior, 2025)

Integrating flavoromics and amplicon sequencing compared the differences in the quality and microbiome of Japanese, Korean, and Chinese style spicy cabbage - Mingwei Zhao; Shijin Xiong; Huiyu Li; Tonghao Du; Xiaoyan Xu; Linli Zhang; Yazhou Xu; Muyan Xiao; Hongbing Ren; Tao Xiong; Mingyong Xie (Food Bioscience, 2025)

Metagenomic Analysis of Gut Microbiome of Persistent Pulmonary Hypertension of the Newborn - Linli Han; Chuyang Lin; Yue Lan; Yimin Hua; Jinlin Wu; Zhenxin Fan; Yifei Li (Cardiovascular Toxicology, 2025)

Cooling benefits from urban planting depend on local background canopy cover: A continental cross-city comparison - Jia Wang; Weiqi Zhou; Haoxin Li; Linli Xu; Honghong Wang (Science of The Total Environment, 2024)

Improving the value of planting and breeding waste compost in agricultural applications: A zucchini cultivation case and circular agricultural models analysis - Jianzhong Tie; Xueqin Gao; Yayu Liu; Wenxu Chen; Linli Hu; Jihua Yu; Tianlai Li (Chemical Engineering Journal, 2024)

Ciprofloxacin Accelerates Angiotensin-II-Induced Vascular Smooth Muscle Cells Senescence Through Modulating AMPK/ROS pathway in Aortic Aneurysm and Dissection - Weiyue Zeng; Yaowen Liang; Shangjun Huang; Jiarui Zhang; Cong Mai; Binbin He; Linli Shi; Baojuan Liu; Weifeng Li; Xiaoran Huang; Xin Li (Cardiovascular Toxicology, 2024)

Enhancing the antioxidant properties and compatibility of protein/sodium alginate film by incorporating Zanthoxylum bungeanum essential oil Pickering emulsion - Linli Wei; Jinsong Li; Xiaoli Qin; Qiang Wang; Jinfeng Zhong (Food Chemistry, 2024)

Citrus transcription factor CsERF098 cooperates with CsWRKY70 to participate in response of fruit to green mold - Ting Li; Wenjun Wang; Qi Chen; Ou Chen; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Ionic liquid for selective extraction of lithium ions from Tibetan salt lake brine with high Na/Li ratio - Rujie Li; Yangyang Wang; Linli Chen; Wenjing Duan; Zhongqi Ren; Zhiyong Zhou (Desalination, 2024)

Polybrominated diphenyl ethers in dust, hair and urine: Exposure, excretion - Junjie Jiang; Tianwei Li; Erde Wang; Yan Zhang; Jiali Han; Linli Tan; Xiang Li; Yuhao Fan; Ye Wu; Qianhui Chen; Jun Jin (Chemosphere, 2024)

A novel CHD7 variant in a chinese family with CHARGE syndrome - Yanhong Shan; LingFang Yao; Linli Li; Xueping Gao; Jinghan Jiang (Genes & Genomics, 2024)

Highly strong and tough silk by feeding silkworms with rare earth ion-modified diets - Haojie Lu; Muqiang Jian; Linli Gan; Yong Zhang; Shuo Li; Xiaoping Liang; Haomin Wang; Mengjia Zhu; Yingying Zhang (Science Bulletin, 2023)

Neutrophil extracellular traps mediate TLR9/Merlin axis to resist ferroptosis and promote triple negative breast cancer progression - Linli Yao; Xiaonan Sheng; Xinrui Dong; Weihang Zhou; Ye Li; Xueyun Ma; Yonggang Song; Huijuan Dai; Yueyao Du (Apoptosis, 2023)

Characteristics of PM2.5 and Its Reactive Oxygen Species in Heating Energy Transition and Estimation of Its Impact on the Environment and Health in China—A Case Study in the Fenwei Plain - Zexuan Wang; Hongmei Xu; Rong Feng; Yunxuan Gu; Jian Sun; Suixin Liu; Ningning Zhang; Dan Li; Tao Wang; Linli Qu; Steven Sai Hang Ho; Zhenxing Shen; et al. (Advances in Atmospheric Sciences, 2023)

A self-regulated transcription factor CsWRKY33 enhances resistance of citrus fruit to Penicillium digitatum - Wenjun Wang; Ting Li; Jialin Chen; Xuan Zhang; Linli Wei; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Transcription factor CsERF1B regulates postharvest citrus fruit resistance to Penicillium digitatum - Ting Li; Wenjun Wang; Qi Chen; Jialin Chen; Xuan Zhang; Linli Wei; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Genome-wide identification of the CsPAL gene family and functional analysis for strengthening green mold resistance in citrus fruit - Linli Wei; Wenjun Wang; Ting Li; Ou Chen; Shixiang Yao; Lili Deng; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Dissimilatory manganese reduction facilitates synergistic cooperation of hydrolysis, acidogenesis, acetogenesis and methanogenesis via promoting microbial interaction during anaerobic digestion of waste activated sludge - Linli Wang; Yangyang Li; Xuesong Yi; Fei Yang; Dexin Wang; Hongjun Han (Environmental Research, 2023)

Research on the Evaluation of Logistics Efficiency in Chinese Coastal Ports Based on the Four-Stage DEA Model - Hui Li; Linli Jiang; Jianan Liu; Dandan Su (Journal of Marine Science and Engineering, 2022)
In the context of economic globalization, coastal port logistics has gradually become a focus of economic development, and the proper management of coastal port logistics performance is the main way to realize the high-efficiency operation of coastal ports, drives the direct economic development of the hinterland, and enhances import and export trade market competitiveness. Accordingly, this study was aimed to measure port logistics efficiency and explore its path of improvement for China’s coastal ports during the 2014–2018 period with a four-stage DEA model, including a Tobit model. The results of this study show that most of the coastal ports in China have emphasized their size more than their planning. During the study period, improving road network construction and the economic level in hinterland port cities was conducive to improving port logistics efficiency, but tertiary industry investment and foreign trade levels were negatively correlated with coastal port logistics efficiency.

The Variability of Air-sea O2 Flux in CMIP6: Implications for Estimating Terrestrial and Oceanic Carbon Sinks - Changyu Li; Jianping Huang; Lei Ding; Yu Ren; Linli An; Xiaoyue Liu; Jiping Huang (Advances in Atmospheric Sciences, 2022)
The measurement of atmospheric O 2 concentrations and related oxygen budget have been used to estimate terrestrial and oceanic carbon uptake. However, a discrepancy remains in assessments of O 2 exchange between ocean and atmosphere (i.e. air-sea O 2 flux), which is one of the major contributors to uncertainties in the O 2 -based estimations of the carbon uptake. Here, we explore the variability of air-sea O 2 flux with the use of outputs from Coupled Model Intercomparison Project phase 6 (CMIP6). The simulated air-sea O 2 flux exhibits an obvious warming-induced upward trend (∼1.49 Tmol yr −2 ) since the mid-1980s, accompanied by a strong decadal variability dominated by oceanic climate modes. We subsequently revise the O 2 -based carbon uptakes in response to this changing air-sea O 2 flux. Our results show that, for the 1990–2000 period, the averaged net ocean and land sinks are 2.10±0.43 and 1.14±0.52 GtC yr −1 respectively, overall consistent with estimates derived by the Global Carbon Project (GCP). An enhanced carbon uptake is found in both land and ocean after year 2000, reflecting the modification of carbon cycle under human activities. Results derived from CMIP5 simulations also investigated in the study allow for comparisons from which we can see the vital importance of oxygen dataset on carbon uptake estimations.

Exosomal miR-486-5p derived from human placental microvascular endothelial cells regulates proliferation and invasion of trophoblasts via targeting IGF1 - Ruixia Ma; Zhijiang Liang; Xiaomei Shi; Linli Xu; Xiaowei Li; Jinhua Wu; Lina Zhao; Guocheng Liu (Human Cell, 2021)
Preeclampsia (PE) is a serious complication of pregnancy. Exosomes are known to be upregulated in PE. In this study, we sought to investigate the effect of miR-486-5p from human placental microvascular endothelial cells, on the function of trophoblast cells. To investigate the function of human placental microvascular endothelial cell (HPVEC)-derived exosomes on trophoblast cells, HPVECs were treated with hypoxia/reoxygenation (H/R). The separation efficiency of exosomes was determined by transmission electron microscopy, nanosight and Western blot. Cell Counting Kit-8, EdU staining, wound-healing, and transwell assay were performed to detect the effect of exosomally transferred miR-486-5p inhibitor on proliferation, migration and invasion of trophoblast cells. MiRDB and dual-luciferase report assay were used to find the target of miR-486-5p. Our data revealed that miR-486-5p was significantly upregulated in H/R-treated HPVEC-Exo, and miR-486-5p was enriched in HPVEC-Exo. miR-486-5p inhibitor carried by HPVEC-Exo significantly inhibited the proliferation, migration and invasion of trophoblast cells. Insulin-like growth factor 1 (IGF1) was found to be the target of miR-486-5p, and IGF1 overexpression notably reversed the effect of miR-486-5p inhibitor from HPVEC-Exo on trophoblast cell function. In summary, H/R-treated HPVEC-derived exosomally expressing miR-486-5p inhibitor significantly inhibited the proliferation, migration and invasion of trophoblast cells via downregulation of IGF1. The findings from the present study may be useful in the development of treatments for PE.

Connective profiles and antagonism between dynamic and static connectivity underlying generalized epilepsy - Sisi Jiang; Hechun Li; Haonan Pei; Linli Liu; Zhiliang Li; Yan Chen; Xiangkui Li; Qifu Li; Dezhong Yao; Cheng Luo (Brain Structure and Function, 2021)

Appropriate Ammonium/Nitrate Mitigates Low Light Stress in Brassica pekinensis by Regulating the Nitrogen Metabolism and Expression Levels of Key Proteins - Linli Hu; Yue Wu; Mohammed Mujitaba Dawuda; Weibiao Liao; Jian Lv; Yutong Li; Jihua Yu; Jianming Xie; Zhi Feng; Guobin Zhang; Alejandro Calderón-Urrea (Journal of Plant Growth Regulation, 2021)

Stimulation of melanin synthesis by UVB is mediated by NO/cGMP/PKG cascade targeting PAK4 in vitro - Linli Xue; Lucheng Chang; Yilei Li; Yanjun Dong; Xiaoyan He (In Vitro Cellular & Developmental Biology - Animal, 2021)

Seasonal behavior of water-soluble organic nitrogen in fine particulate matter (PM2.5) at urban coastal environments in Hong Kong - Steven Sai Hang Ho; Lijuan Li; Linli Qu; Junji Cao; Ka Hei Lui; Xinyi Niu; Shun-Cheng Lee; Kin Fai Ho (Air Quality, Atmosphere & Health, 2019)

Improved Sp1 and Betaine Homocysteine-S-Methyltransferase Expression and Homocysteine Clearance Are Involved in the Effects of Zinc on Oxidative Stress in High-Fat-Diet-Pretreated Mice - Li Wu; Xihong Zhou; Tiejun Li; Juyun He; Linli Huang; Zicheng Ouyang; Liuqin He; Tao Wei; Qinghua He (Biological Trace Element Research, 2018)

Brain REST/NRSF Is Not Only a Silent Repressor but Also an Active Protector - Yangang Zhao; Min Zhu; Yanlan Yu; Linli Qiu; Yuanyuan Zhang; Li He; Jiqiang Zhang (Molecular Neurobiology, 2017)

Relationship between parental genetic distance and offspring’s heterosis for early growth traits in Liriodendron: implication for parent pair selection in cross breeding - Junxiu Yao; Huogen Li; Jing Ye; Linli Shi (New Forests, 2016)

Production of Brassica tri-genomic vegetable germplasm by hybridisation between tuber mustard (Brassica juncea) and red cabbage (B. oleracea) - Junxing Li; Linli Rao; Qiufeng Meng; Muhammad Awais Ghani; Liping Chen (Euphytica, 2015)

Endogenous Salicylic Acid Levels and Signaling Positively Regulate Arabidopsis Response to Polyethylene Glycol-Simulated Drought Stress - Qingqing He; Shiyang Zhao; Qunfei Ma; Yiyan Zhang; Linli Huang; Guangzhe Li; Lin Hao (Journal of Plant Growth Regulation, 2014)

Effects of breeds and dietary protein levels on the growth performance, energy expenditure and expression of avUCP mRNA in chickens - Qihua Li; Zhiqiang Xu; L. Liu; Hongxin Yu; Hua Rong; Linli Tao; Xi Zhang; Xiaobo Chen; Dahai Gu; Yueyuan Fan; Xiaoqin Li; Changrong Ge; et al. (Molecular Biology Reports, 2013)

Urban transformation of a metropolis and its environmental impacts - Zhan Tian; Guiying Cao; Jun Shi; Ian McCallum; Linli Cui; Dongli Fan; Xinhu Li (Environmental Science and Pollution Research, 2012)

Detection of Bifidobacterium Species-specific 16S rDNA Based on QD FRET Bioprobe - JunFeng Jiang; ZhiHui Peng; Le Deng; Guang Li; LinLi Chen (Journal of Fluorescence, 2010)

Groundwater quality and land use change in a typical karst agricultural region: a case study of Xiaojiang watershed, Yunnan - Yongjun Jiang; Daoxian Yuan; Shiyou Xie; Linli Li; Gui Zhang; Raosheng He (Journal of Geographical Sciences, 2006)